Russian-Chinese Relations: Political and Economic Aspect - O. E. Grishin; A. V. Trofimova (Проблемы постсоветского пространства)
International relations play a vital role in modern politics. They differ from any other relations by several features: spontaneity, lack of a single core of power and the center for making centralized decisions, coverage of all spheres of life of the participants involved in the process and the increasing influence of subjective factors. The scale that embraces international relations differs in «verticals» and «contours». They include global, regional and specific relationships, as well as group and bilateral relations.China and Russia are connected by centuries-old history. Russian-Chinese relations and their dynamic development are of interest to the political science community. At present, they form an important material basis for cooperation in the areas of trade and economy, contributing to the development of the Russian economy.China supports and subsidizes projects that ensure its interests in Russia. Political and economic cooperation between Russia and China is developing actively and is using more and more resources. The more important it becomes to maintain good-neighbor and productive relations. Russian-Chinese relations affect many spheres of life of the two States: scientific, economic, military, cultural, etc.in this light, economic cooperation stands out as one of the main. Russian-Chinese trade and economic cooperation is actively analyzed in the works of many researchers, but there is no consensus on the most important vectors of cooperation and prospects for its development. In this regard, the analysis and structuring of some areas of Russian-Chinese relations, foreign economic relations, opportunities for the development of relations between Russia and China, as well as their transition to a new level are becoming urgent.China is the largest trade partner of Russia and an investor who is interested in promoting some projects implemented in Russia. For this reason, the development of successful and fruitful relations is in the first place among the leaders of the two powers. The need for multidirectional trade and economic relations is also conditioned by geopolitical, cultural and historical factors.